Application of Simulation Learning Models in Improving Motivation and Learning Outcomes of Accounting Information System Subject - Okto Irianto (Journal of Economics and Business Letters, 2021)
The purpose of this study is to improve student motivation and learning outcomes in Accounting Information System subject through the application of simulation learning models. The type of research conducted is Classroom Action Research (CAR) which consists of two cycles and 6 meetings. The study was conducted in Even Semester 2020/2021 in the Accounting Department, Faculty of Economics and Business, Musamus University, Merauke. The research sample was 50 Accounting Department students. The results showed that the motivation of students in the first cycle reached 27.30% in the high category experienced an increase in the second cycle which reached 60.20% in the high category. Student learning outcomes also increased where in the pre-cycle the average student score reached 48.04, in the first cycle it reached 63.55, and in the second cycle it reached 74.16. In conclusion, the simulation learning model can increase motivation and learning outcomes of Accounting Information System subject at Musamus University.